IDENTIFIKASI DAN ANALISIS POTENSI KELURAHAN KARANG RIA DALAM MENDUKUNG PENGEMBANGAN DESTINASI WISATA LOKAL - Kondoj, Telly Hetty Isje; Sendow, Deby Christiani; Takaendengan, Mita Erdiaty; Lagarense, Bet El Silisna (PolimdoSains, 2026)
Manado City is one of the cities known as a Tourist Destination Area in the Eastern Region of Indonesia. The Manado City Government wants to develop sectors that are directly related to economic improvement, including the Tourism sector. Daseng Karangria is one of the potential culinary tourism areas that supports the development of tourism in Manado City. This research aims to identify the potentials of Daseng Karangria Culinary Tourism. A qualitative descriptive method is used in this study using a SWOT (Stenght, Weakness, Oppurtunity, Threats) analysis approach . The data collection technique is to make observations in the field and communicate with MSMEs, visitors and the local government. And the results show that Daseng Karangria has a strong culinary tourism potential supported by infrastructure, infrastructure, visitors, income and various types of food and beverage culinary menus. This study concludes that Daseng Karangria has great potential in supporting tourism in Manado City, and the right development and promotion can further maximize its contribution to the tourism sector.